Nanosphere Lithography: State-of-the-art and Future Directions - Lindner, Jörg

TEM Characterization of Nickel Nanodot Arrays on Silicon formed by Nanosphere Lithography - Pauly, Johannes; Lindner, Jörg

Nanokugellithographie: Grundlagen und Anwendungen - Lindner, Jörg

Nanolithographie von Oberflächen für das Wachstum optoelektronischer Strukturen - Lindner, Jörg

Dual-polarity plasmonic metalens for visible light - Chen, Xianzhong; Huang, Lingling; Mühlenbernd, Holger; Li, Guixin; Bai, Benfeng; Tan, Qiaofeng; Jin, Guofan; Qiu, Cheng-Wei; Zhang, Shuang; Zentgraf, Thomas (Nature Communications)

Vibrational fingerprints of LiNbO3-LiTaO3 mixed crystals - Sanna, Simone; Riefer, Arthur; Neufeld, Sergej; Schmidt, Wolf Gero; Berth, Gerhard; Widhalm, Alex; Zrenner, Artur (Proceedings of ISAF-ECAPD-PFM 2012)
The structural and vibrational properties of lithium niobate (LN) – lithium tantalate (LT) mixed crystals (LNT, LiNb1-xTaxO3) are investigated over the whole composition range by first-principles simulations. The crystal volume grows roughly linearly from LT to LN, whereby the lattice parameters a and c show minor deviations from the Vegard behavior between the end compounds, LiNbO3 and LiTaO3. Our calculations in the framework of the density functional theory show the TO1, TO2 and TO4-modes to become harder with increasing Nb concentration. TO3 becomes softer with increasing Nb content, instead. The frequency shifts of the zone center A1-TO phonon modes for crystals with different compositions are found to be as large as 30 cm-1. Raman spectroscopy, which is sensitive to the A1 modes, can be therefore employed to determine the crystal composition.
Keywords: Ferroelectrics; Vibrational properties; LiNbO3; LiTaO3; Mixed Crystals

Coherent optoelectronics with quantum dots - Michaelis de Vasconcellos, Steffen; Gordon, Simon; Mantei, Dirk; Leier, Yves Alexander; Al-Hmoud, M.; Quiring, Wadim; Zrenner, Artur (QUANTUM OPTICS WITH SEMICONDUCTOR NANOSTRUCTURES)
Coherent physics and applications of exciton qubits in electric fi eld tunable quantum dot structures are our focus. Excitations with picosecond (ps) laser pulses result in qubit rotations. Using state projection by tunnelling the readout can be performed in quantitative way. As a function of electric fi eld induced detuning Ramsey fringes of a single exciton qubit can be observed and controlled for double pulse excitation. Therefore it is possible to demonstrate voltage controlled qubit manipulations within a wide range of pulse delays. Using fast electric signals, phase-locked to ps-laser pulses, the coherent control of an exciton qubit can be obtained by electric interaction. Such voltage controlled qubit manipulations seem to be essential for new types of optoelectronic quantum gates and novel applications in the fi eld of coherent optoelectronics.
Keywords: excitons; quantum bits; coherent manipulation; Ramsey interference; quantum gate

Dispersionless Phase Discontinuities for Controlling Light Propagation - Huang, Lingling; Chen, Xianzhong; Mühlenbernd, Holger; Li, Guixin; Bai, Benfeng; Tan, Qiaofeng; Jin, Guofan; Zentgraf, Thomas; Zhang, Shuang (Nano Letters)

Mapping the near-field dynamics in plasmon-induced transparency - Ye, Ziliang; Zhang, Shuang; Wang, Yuan; Park, Yong-Shik; Zentgraf, Thomas; Bartal, Guy; Yin, Xiaobo; Zhang, Xiang (Physical Review B)

Compact Magnetic Antennas for Directional Excitation of Surface Plasmons - Liu, Yongmin; Palomba, Stefano; Park, Yongshik; Zentgraf, Thomas; Yin, Xiaobo; Zhang, Xiang (Nano Letters)

Control of plasmon dynamics in coupled plasmonic hybrid mode microcavities - Lanzillotti-Kimura, N. D.; Zentgraf, Thomas; Zhang, X. (Physical Review B)

Slow-light dispersion by transparent waveguide plasmon polaritons - Ishikawa, Atsushi; Oulton, Rupert F.; Zentgraf, Thomas; Zhang, Xiang (Physical Review B)

Spectral Signatures of Polarons in Conjugated Co-polymers - Wiebeler, Christian; Tautz, Raphael; Feldmann, Jochen; von Hauff, Elizabeth; Da Como, Enrico; Schumacher, Stefan (The Journal of Physical Chemistry B)

Dynamics of fluorescence depolarisation in star-shaped oligofluorene-truxene molecules - Montgomery, Neil A.; Hedley, Gordon J.; Ruseckas, Arvydas; Denis, Jean-Christophe; Schumacher, Stefan; Kanibolotsky, Alexander L.; Skabara, Peter J.; Galbraith, Ian; Turnbull, Graham A.; Samuel, Ifor D. W. (Physical Chemistry Chemical Physics)

Multiphoton state engineering by heralded interference between single photons and coherent states - Bartley, Tim; Donati, Gaia; Spring, Justin B.; Jin, Xian-Min; Barbieri, Marco; Datta, Animesh; Smith, Brian J.; Walmsley, Ian A. (Physical Review A)

Substrate Induced Thermal Decomposition of Perfluoro-Pentacene Thin Films on the Coinage Metals - Schmidt, Christian; Breuer, Tobias; Wippermann, Stefan; Schmidt, Wolf Gero; Witte, Gregor (The Journal of Physical Chemistry C)

Atomistic Picture of Charge Density Wave Formation at Surfaces - Wall, Simone; Krenzer, Boris; Wippermann, Stefan; Sanna, Simone; Klasing, Friedrich; Hanisch-Blicharski, Anja; Kammler, Martin; Schmidt, Wolf Gero; Horn-von Hoegen, Michael (Physical Review Letters)

Ferroelectric phase transition in LiNbO3: Insights from molecular dynamics - Sanna, S.; Schmidt, Wolf Gero (IEEE Transactions on Ultrasonics, Ferroelectrics and Frequency Control)

Linear and nonlinear optical response of LiNbO3 calculated from first principles - Riefer, Arthur; Sanna, Simone; Gavrilenko, Alexander V.; Schmidt, Wolf Gero (IEEE Transactions on Ultrasonics, Ferroelectrics, and Frequency Control)

Polarization-dependent methanol adsorption on lithium niobate Z-cut surfaces - Riefer, A.; Sanna, S.; Schmidt, Wolf Gero (Physical Review B)

Atomic-resolution imaging of the polar (0001¯) surface of LiNbO3in aqueous solution by frequency modulation atomic force microscopy - Rode, S.; Hölscher, R.; Sanna, S.; Klassen, S.; Kobayashi, K.; Yamada, H.; Schmidt, Wolf Gero; Kühnle, A. (Physical Review B)

Fingerprints of order and disorder in the electronic and optical properties of crystalline and amorphous TiO2 - Landmann, M.; Köhler, T.; Köppen, S.; Rauls, E.; Frauenheim, T.; Schmidt, Wolf Gero (Physical Review B)

Activation of Surface Hydroxyl Groups by Modification of H-Terminated Si(111) Surfaces - Thissen, Peter; Peixoto, Tatiana; Longo, Roberto C.; Peng, Weina; Schmidt, Wolf Gero; Cho, Kyeongjae; Chabal, Yves J. (Journal of the American Chemical Society)

Interplay between metal-free phthalocyanine molecules and Au(110) substrates - Rauls, E.; Schmidt, Wolf Gero; Pertram, T.; Wandelt, K. (Surface Science)

The electronic structure and optical response of rutile, anatase and brookite TiO2 - Landmann, M; Rauls, E; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

2-Aminopyrimidine-silver(I) based organic semiconductors: Electronic structure and optical response - Riefer, A.; Rauls, E.; Schmidt, Wolf Gero; Eberhard, J.; Stoll, I.; Mattay, J. (Physical Review B)

pH-dependent structure and energetics of H2O/MgO(100) - Thissen, Peter; Thissen, Vera; Wippermann, Stefan; Chabal, Yves J.; Grundmeier, Guido; Schmidt, Wolf Gero (Surface Science)

Adsorption of OH and H at the LiNbO3(0001) surface - Hölscher, R.; Sanna, S.; Schmidt, Wolf Gero (physica status solidi (c))

In-Si(111)(4 × 1)/(8 × 2) nanowires: Electron transport, entropy, and metal-insulator transition - Schmidt, Wolf Gero; Wippermann, S.; Sanna, S.; Babilon, M.; Vollmers, N. J.; Gerstmann, Uwe (physica status solidi (b))

All-optical tunability of microdisk lasers via photo-adressable polyelectrolyte functionalization - Piegdon, K. A.; Lexow, M.; Grundmeier, G.; Kitzerow, Heinz-Siegfried; Pärschke, K.; Mergel, D.; Reuter, Dirk; Wieck, A. D.; Meier, Cedrik (Optics Express)

All-optical tunability of microdisk lasers via photo-adressable polyelectrolyte functionalization - Piegdon, K. A.; Lexow, M.; Grundmeier, G.; Kitzerow, Heinz-Siegfried; Pärschke, K.; Mergel, D.; Reuter, Dirk; Wieck, A. D.; Meier, C. (Optics Express)

Cavity-assisted emission of polarization-entangled photons from biexcitons in quantum dots with fine-structure splitting - Schumacher, Stefan; Förstner, Jens; Zrenner, Artur; Florian, Matthias; Gies, Christopher; Gartner, Paul; Jahnke, Frank (Optics Express)
We study the quantum properties and statistics of photons emitted by a quantum-dot biexciton inside a cavity. In the biexciton-exciton cascade, fine-structure splitting between exciton levels degrades polarization-entanglement for the emitted pair of photons. However, here we show that the polarization-entanglement can be preserved in such a system through simultaneous emission of two degenerate photons into cavity modes tuned to half the biexciton energy. Based on detailed theoretical calculations for realistic quantum-dot and cavity parameters, we quantify the degree of achievable entanglement.
Keywords: tet_topic_qd

Optimization of the intensity enhancement in plasmonic nanoantennas - Hildebrandt, Andre; Reichelt, Matthias; Meier, Torsten; Förstner, Jens
We design the geometrical shape of plasmonic nanostructures to achieve field patterns with desired properties. For this, we combine Maxwell simulations and automatic optimization techniques. By allowing variations of the geometrical shape, which can be based on either boxes or arbitrary polygons, we maximize the desired objective.
Keywords: tet_topic_optical antenna; tet_topic_plasmonics

A 2D Quantum Walk Simulation of Two-Particle Dynamics - Schreiber, Andreas; Gábris, Aurél; Rohde, Peter P.; Laiho, Kaisa; Štefaňák, Martin; Potoček, Václav; Hamilton, Craig; Jex, Igor; Silberhorn, Christine (Science)
Here, There, Everywhere Random walks are a powerful mathematical method that can be used to simulate certain processes in biology, chemistry, or even the stock market. They present a statistical method for mapping the possible routes that processes can take. Quantum walks are expected to be able to probe multiple paths simultaneously. Quantum walks have been demonstrated for one-dimensional, or straight-line, walks. Now, Schreiber et al. (p. 55 , published online 8 March) demonstrate an optical system that can simulate quantum walks over a two-dimensional system, thereby providing the capability of describing much more complex processes.
Keywords: Multidisciplinary

Limits on the deterministic creation of pure single-photon states using parametric down-conversion - Christ, Andreas; Silberhorn, Christine (Physical Review A)
Keywords: Atomic and Molecular Physics; and Optics

Dynamics of ionisation and entanglement in the 'atom + quantum electromagnetic field' system - Sharapova, Polina; Tikhonova, O V (Quantum Electronics)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Statistical and Nonlinear Physics; Electronic; Optical and Magnetic Materials

„Praktische Aktivitäten“ im physikbezogenen Sachunterricht der Grundschule und im physikalischen Anfangsunterricht der Sekundarstufe – ein Vergleich. - Tenberge, Claudia; Lange, Kim; Möller, Kornalia (Bedingungen des Lehrens und Lernens in der Grundschule – Bilanz und Perspektiven.)

High resolution time-to-space conversion of sub-picosecond pulses at 155µm by non-degenerate SFG in PPLN crystal - Shayovitz, Dror; Herrmann, Harald; Sohler, Wolfgang; Ricken, Raimund; Silberhorn, Christine; Marom, Dan M. (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Exponentially enhanced quantum communication rate by multiplexing continuous-variable teleportation - Christ, Andreas; Lupo, Cosmo; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

Characteristics of displaced single photons attained via higher order factorial moments - Laiho, Kaisa; Avenhaus, Malte; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

First-principles and empirical potential simulation study of intrinsic and carbon-related defects in silicon - Zirkelbach, F.; Stritzker, B.; Nordlund, K.; Schmidt, Wolf Gero; Rauls, E.; Lindner, Jörg K. N. (physica status solidi (c))
Results of atomistic simulations aimed at understanding precipitation of the highly attractive wide band gap semiconductor material silicon carbide in silicon are presented. The study involves a systematic investigation of intrinsic and carbon-related defects as well as defect combinations and defect migration by both, quantummechanical first-principles as well as empirical potential methods. Comparing formation and activation energies, ground-state structures of defects and defect combinations as well as energetically favorable agglomeration of defects are predicted. Moreover, accurate ab initio calculations unveil limitations of the analytical method based on a Tersoff-like bond order potential. A work-around is proposed in order to subsequently apply the highly efficient technique on large structures not accessible by first-principles methods. The outcome of both types of simulation provides a basic microscopic understanding of defect formation and structural evolution particularly at non-equilibrium conditions strongly deviated from the ground state as commonly found in SiC growth processes. A possible precipitation mechanism, which conforms well to experimental findings and clarifies contradictory views present in the literature is outlined.

Collective Effects in Second-Harmonic Generation from Split-Ring-Resonator Arrays - Linden, S.; Niesler, F. B. P.; Förstner, Jens; Grynko, Yevgen; Meier, Torsten; Wegener, M. (Physical Review Letters)
Optical experiments on second-harmonic generation from split-ring-resonator square arrays show a nonmonotonic dependence of the conversion efficiency on the lattice constant. This finding is interpreted in terms of a competition between dilution effects and linewidth or near-field changes due to interactions among the individual elements in the array.
Keywords: tet_topic_shg; tet_topic_meta

Excitonic Eigenstates of Disordered Semiconductor Quantum Wires: Adaptive Wavelet Computation of Eigenvalues for the Electron-Hole Schrödinger Equation - Meier, Torsten; Mollet, Christian; Kunoth, Angela (Communications in Computational Physics)
A novel adaptive approach to compute the eigenenergies and eigenfunctions of the two-particle (electron-hole) Schrödinger equation including Coulomb attraction is presented. As an example, we analyze the energetically lowest exciton state of a thin one-dimensional semiconductor quantum wire in the presence of disorder which arises from the non-smooth interface between the wire and surrounding material. The eigenvalues of the corresponding Schrödinger equation, i.e., the one-dimensional exciton Wannier equation with disorder, correspond to the energies of excitons in the quantum wire. The wavefunctions, in turn, provide information on the optical properties of the wire. We reformulate the problem of two interacting particles that both can move in one dimension as a stationary eigenvalue problem with two spacial dimensions in an appropriate weak form whose bilinear form is arranged to be symmetric, continuous, and coercive. The disorder of the wire is modelled by adding a potential in the Hamiltonian which is generated by normally distributed random numbers. The numerical solution of this problem is based on adaptive wavelets. Our scheme allows for a convergence proof of the resulting scheme together with complexity estimates. Numerical examples demonstrate the behavior of the smallest eigenvalue, the ground state energies of the exciton, together with the eigenstates depending on the strength and spatial correlation of disorder.

Photonic crystal waveguides intersection for resonant quantum dot optical spectroscopy detection - Song, Xiaohong; Declair, Stefan; Meier, Torsten; Zrenner, Artur; Förstner, Jens (Optics Express)
Using a finite-difference time-domain method, we theoretically investigate the optical spectra of crossing perpendicular photonic crystal waveguides with quantum dots embedded in the central rod. The waveguides are designed so that the light mainly propagates along one direction and the cross talk is greatly reduced in the transverse direction. It is shown that when a quantum dot (QD) is resonant with the cavity, strong coupling can be observed via both the transmission and crosstalk spectrum. If the cavity is far off-resonant from the QD, both the cavity mode and the QD signal can be detected in the transverse direction since the laser field is greatly suppressed in this direction. This structure could have strong implications for resonant excitation and in-plane detection of QD optical spectroscopy.
Keywords: tet_topic_phc; tet_topic_qd

Near-field coupling and second-harmonic generation in split-ring resonator arrays - Grynko, Yevgen; Meier, Torsten; Linden, Stefan; Niesler, Fabian B. P.; Wegener, Martin; Förstner, Jens
We simulate the linear and nonlinear optical response from split-ring resonator (SRR) arrays to study collective effects between the constituent SRRs that determine spectral properties of the second harmonic generation (SHG). We apply the Discontinuous Galerkin Time Domain (DGTD) method and the hydrodynamic Maxwell-Vlasov model to calculate the SHG emission. Our model is able to qualitatively reproduce and explain the non-monotonic dependence of the spectral SHG transmission measured experimentally for SRR arrays with different lattice constants
Keywords: tet_topic_meta; tet_topic_shg

Engineering high harmonic generation in semiconductors via pulse shaping - Reichelt, Matthias; Hildebrandt, Andre; Walther, Andrea; Förstner, Jens; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XVI)
Paper Abstract High harmonic generation is investigated for a two-band model of a semiconductor nanostructure. Similar to an atomic two-level system, the semiconductor emits high harmonic radiation. We show how one can specifically enhance the emission for a given frequency by applying a non-trivially shaped laser pulse. Therefore, the semiconductor Bloch equations including the interband and additionally the intraband dynamics are solved numerically and the spectral shape of the input pulse is computed via an optimization algorithm. It is demonstrated that desired emission frequencies can be favored even though the overall input power is kept constant. We also suggest special metallic nano geometries to achieve enhanced localized optical fields. They are found by geometric optimization.
Keywords: tet_topic_shg

Tailoring the high-harmonic emission in two-level systems and semiconductors by pulse shaping - Reichelt, Matthias; Walther, Andrea; Meier, Torsten (Journal of the Optical Society of America B)
The generation of specific high harmonics for an optical two-level system is elucidated. The desired emitted radiation can be induced by a carefully designed excitation pulse, which is found by a multiparameter optimization procedure. The presented mechanism can also be applied to semiconductor structures for which the calculations result in much higher emission frequencies. The optimization procedure is either performed using a genetic algorithm or a rigorous mathematical optimization technique.

Die professionelle Kompetenz angehender Physiklehrkräfte in verschiedenen Ausbildungsformen - Riese, Josef; Reinhold, Peter (Zeitschrift für Erziehungswissenschaft)
Keywords: Education

Kompetenzen von Lehramtsstudierenden in Physik - Riese, Josef; Reinhold, Peter (Formate Fachdidaktischer Forschung. Empirische Projekte – historische Analysen – theoretische Grundlegungen)

Fachdidaktisches Wissen von Lehramtsstudierenden und Lehrenden an der Hochschule im Fach Physik - Gramzow, Yvonne; Riese, Josef; Reinhold, Peter (Konzepte fachdidaktischer Strukturierung für den Unterricht)